High-stakes Testing: Another Analysis - Rosenshine, Barak (Education Policy Analysis Archives, 2003)
Amrein and Berliner (2002b) compared National Assessment of Educational Progress (NAEP) results in high-stakes states against the national average for NAEP scores. They studied NAEP scores for 8th grade mathematics, 4th grade mathematics, and 4th grade reading. They concluded that states that introduced consequences (high-stakes) to their statewide tests did not show any particular gains in their statewide NAEP scores. However, there was no comparison group in their analysis. In this analysis, a comparison group was formed from states that did not attach consequences to their state-wide tests. This analysis showed that states that attached consequences outperformed the comparison group of states on each of the three NAEP tests for the last four-year period. These results showed that, overall, these was a meaningful carryover from attaching consequences on statewide tests to statewide NAEP scores.